2016
DOI: 10.1016/j.otsr.2016.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Clinical results of endoscopic treatment without repair for partial thickness gluteal tears

Abstract: IV, retrospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 21 publications
0
12
0
1
Order By: Relevance
“…10,11 In some patients with recalcitrant lateral hip pain, an ITB release with or without a trochanteric bursectomy is adequate to resolve their symptoms, such as the patients described by Jain et al 11 and Zeman et al 21 In these cases, pain may be caused by the ITB rubbing along the underlying tissues, with the friction creating painful inflammation. 10 However, addressing the ITB is only part of the problem for many patients with GTPS, as shown in a study by Coulomb et al, 8 in which patients with GTPS and confirmed partial-thickness gluteus medius tears underwent surgery involving ITB release, bursectomy, and debridement of the fraying gluteus medius. Of the 17 patients, 6 were unsatisfied, and many had only a moderate improvement in PROs and functional results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10,11 In some patients with recalcitrant lateral hip pain, an ITB release with or without a trochanteric bursectomy is adequate to resolve their symptoms, such as the patients described by Jain et al 11 and Zeman et al 21 In these cases, pain may be caused by the ITB rubbing along the underlying tissues, with the friction creating painful inflammation. 10 However, addressing the ITB is only part of the problem for many patients with GTPS, as shown in a study by Coulomb et al, 8 in which patients with GTPS and confirmed partial-thickness gluteus medius tears underwent surgery involving ITB release, bursectomy, and debridement of the fraying gluteus medius. Of the 17 patients, 6 were unsatisfied, and many had only a moderate improvement in PROs and functional results.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 17 patients, 6 were unsatisfied, and many had only a moderate improvement in PROs and functional results. 8 Thus, releasing the ITB is an important component of addressing GTPS, but in patients with complex hip pathology, it does not have a high likelihood of consistently resolving the hip symptoms as an isolated procedure. 8 It should also be acknowledged that ITB release is not a wholly benign procedure, with one example being concerns about slowed return to performance after ITB release in athletic populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sonography was the preferred imaging technique in 6 studies, 10,23,32,33,36,39 MRI and sonography were used in 3 studies, 25,26,37 and MRI or sonography was used in 2 studies. 4,14 Outcome Measures A variety of outcome measures was used across the included studies to assess treatment success. Pain was most commonly assessed using a visual analog scale (VAS; 16 studies {{ ) or numeric rating scale (NRS; 2 studies 10,42,51 ).…”
Section: Diagnosismentioning
confidence: 99%
“…Rarely used measures for the determination of outcomes were the Lower Extremity Functional Scale, 10,18 Nonarthritic Hip Score, 29,53 and Merle D'Aubigné-Postel score 17,55 in 2 studies each. The Oswestry Disability Index, 23 EuroQol-5 Dimensions, 42 Victorian Institute of Sport Assessment-Gluteal Tendon, 42 International Hip Outcome Tool (iHOT-33 37 /iHOT-12 50 ), lateral hip pain questionnaire, 42 Lequesne index, 38 University of California Los Angeles activity scale, 14 or Western Ontario and McMaster Universities Arthritis Index 4 was used in 1 study each.…”
Section: Diagnosismentioning
confidence: 99%